The Dung Beetle Compass - Dacke, Marie; Jundi, Basil El (Current biology, 2018)
What do a burly rower, a backstroke swimmer and a hard-working South African dung beetle all have in common? The answer is: they all benefit from moving along a straight path, and do so moving backwards. This, however, is where the similarity ends. While the rower has solved this navigational challenge by handing the task of steering to the coxswain, who faces the direction of travel, and the swimmer is guided down her lane by colourful ropes, the beetle puts its faith in the sky. From here, it utilises a larger repertoire of celestial compass cues than is known to be used by any other animal studied to date. A robust internal compass, designed to interpret directional information, has evolved under the selective pressure of shifting today's lunch efficiently out of reach of competitors, also drawn to the common buffet. While this is a goal that beetles might share with the hungry athletes, they reach it with drastically different brain powers; the brain of the beetle is several times smaller than a match head, containing fewer than a million neurons.